Contextual Learning Strategy in the Digital Era at Aisyiyah Fullday Elementary School, Klaten - Badroh Rif'ati (Al-Hayat: Journal of Islamic Education, 2020)
The purpose of this study is to identify contextual learning problems in schools and their application in the digital era, where children today tend to return to a perspective that children will learn better if the environment in which they study is a natural environment. This paper is the result of research that uses a logical phenomenon approach, the suggestions and recommendations of this study are expected to increase learning knowledge for both parents, teachers and students to succeed in improving learning outcomes. The method used is qualitative in the form of qualitative descriptive analysis, with semi-structured interviews, focus groups, and participant observation. The findings in this study are that contextual learning at Aisyiyah Fullday Pandes Wedi Elementary School, Klaten, Central Java is accompanied by textual understanding so that there is a student activation process (acquiring knowledge), so students will understand the material optimally.